Lower respiratory tract infections among human immunodeficiency virus-exposed, uninfected infants - Mussi-Pinhata, Marisa M (2010)
OBJECTIVES: To evaluate whether maternal HIV disease severity during pregnancy is associated with an increased likelihood of lower respiratory tract infections (LRTIs) in HIV-exposed, uninfected infants. METHODS: HIV-exposed, uninfected, singleton, term infants enrolled in the NISDI Perinatal Study, with birth weight ≥ 2500 grams were followed from birth until six months of age. LRTI diagnoses, hospitalizations, and associated factors were assessed. RESULTS: Of 547 infants, 103 (18.8%) experienced 116 episodes of LRTIs (incidence=0.84 LRTIs/100 child-weeks). Most (81%) episodes were bronchiolitis. Forty-nine (9.0%) infants were hospitalized at least once with an LRTI. There were 53 hospitalizations (45.7%) for 116 LRTI episodes. None of these infants were breastfed. The odds of LRTI in infants whose mothers had CD4%<14 were 4.4 times than that of those whose mothers had CD4%≥29 (p=0.003). The odds of LRTI were 16.0 times that of infants with a CD4+ count [cells/mm3] < 750 at birth compared to those with CD4+≥750 (p=0.002). Maternal CD4+ decline and Infant hemoglobin at the 6-12 week visit were associated with infant LRTIs after 6-12 weeks and before six months of age. CONCLUSIONS: Acute bronchiolitis is common and frequently severe among HIV-exposed, uninfected infants aged six months or less. Lower maternal and infant CD4+ values were associated with a higher risk of infant LRTIs. Further understanding of the immunological mechanisms of severe LRTIs is needed.